Assessment of Factors Affecting Competitiveness of Fruit and Vegetable Products: In Case Uzbekistan - Odilovich, Imomov Jamshidkhon (International Journal of Psychosocial Rehabilitation, 2020)
According to international experts, the number of people suffering from hunger as a result of the pandemic will double to 1.6 billion. The development of agriculture, the scarcity of resources, and at the same time the pollution of the environment pose a serious problem for the growing population in terms of nutrition. This article identifies the factors influencing the competitiveness of fruit and vegetable products and evaluates them on the basis of correlation-regression models. The results can be used to increase the competitiveness of the fruit and vegetable industry.